APPLICATION OF ARCHITECTURAL SEMIOTICS IN THE DIGITAL ERA - Ayub Muktiono (INFOKUM, 2022)
The digital era brings changes in architectural paradigms, presenting new challenges in the interpretation and understanding of architectural aesthetics. This research aims to explore the meaning and symbolism in digital architecture in the era of information and communication technology. This research method includes semiotic analysis of virtual building structures, considering visual, audio and interactive elements. Data collection was carried out through literature studies with a qualitative approach. The results of this research state that the application of architectural semiotic concepts in the digital era has a significant impact on the way users interact and understand digital spaces. In this context, visual elements such as icons, symbols and colors not only function as aesthetic elements, but also as a language that provides instructions and information to users. Likewise, the use of sound and music is identified as a semiotic element that can create additional atmosphere and emotions in digital environments. This integration of semiotics not only improves the clarity and readability of information, but also creates a richer and more contextual user experience.